ONLINE AND E-LEARNING BEST PRACTICES, NEEDS AND HABITS FOR THE INTERNATIONAL AGRIMBA NETWORK - Kovács, Krisztián; Péntek, Ádám; Nábrádi, András; Juračak, Josip; Šakić Bobić, Branka; Malak Rawlikowska, Agata; Kurek, Katarzyna A.; Heijman, Wim; Bielik, Peter; Bullová, Tatiana; Litvin, Aurelia (Applied Studies in Agribusiness and Commerce, 2023)
From the literature part of this research, it shows that, some of the most popular Learning Management Systems (LMS), such as Moodle, Canvas and Blackboard, are used by many universities and colleges worldwide and their popularity is steadily increasing as more institutions adopt online learning. The usage statistics of LMSs by universities can be influenced by a number of factors, such as the size of the university, the specific requirements of the institution, the availability of alternative solutions, and the preferences of faculty and students. In addition, the popularity of LMSs among universities may change over time as new systems enter the market or as existing systems improve and evolve. Based on the number of customers, Moodle's three biggest competitors in the learning management systems category are Google Classroom with 11.70%, LinkedIn Learning with 8.87% and TalentLMS with 5.16% market share.The most frequently used functionalities of the e-learning system are: study content creation, course management and content library, and the least frequently used are integration with other systems, multilanguage utility, plagiarism checking, accessibility to people with disabilities and personalized learning. Similarly, the most popular functionalities are course management, study content creation and assessment and testing. Respondents least liked the functions of integration with other systems, webinars, accessibility for inclusion, and video hosting and streaming.Lectures or slides are most often uploaded to platforms, followed by written materials and links, then videos, pictures and tables. Judging by the answers received, the majority of respondents are either completely satisfied (34%) or moderately satisfied (42%) with the e-learning systems they are using now.